Isolation of Novel Adenovirus from Fruit Bat ( Pteropus dasymallus yayeyamae ) - Maeda, Ken; Hondo, Eiichi; Terakawa, Junpei; Kiso, Yasuo; Nakaichi, Numekazu; Endoh, Daiji; Sakai, Kouji; Morikawa, Shigeru; Mizutani, Tetsuya (Emerging infectious diseases, 2008)
Isolation of Novel Adenovirus from Fruit Bat